2014
DOI: 10.1186/1471-2156-15-46
|View full text |Cite
|
Sign up to set email alerts
|

A gain-of-function screen to identify genes that reduce lifespan in the adult of Drosophila melanogaster

Abstract: BackgroundSeveral lines of evidence associate misregulated genetic expression with risk factors for diabetes, Alzheimer’s, and other diseases that sporadically develop in healthy adults with no background of hereditary disorders. Thus, we are interested in genes that may be expressed normally through parts of an individual’s life, but can cause physiological defects and disease when misexpressed in adulthood.ResultsWe attempted to identify these genes in a model organism by arbitrarily misexpressing specific g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…Information on these genes and their expression profiles is currently scarce. However, both genes were found to regulate Drosophila lifespan [ 37 , 38 ], suggesting some caution in the interpretation the longevity experiments, in which the elav -Gal4 drivers were used [ 39 41 ]. In addition, the CG16779 gene is predicted to encode a factor involved in regulation of Choline acetyltransferase (ChAT), which is responsible for the synthesis of the neurotransmitter acetylcholine [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Information on these genes and their expression profiles is currently scarce. However, both genes were found to regulate Drosophila lifespan [ 37 , 38 ], suggesting some caution in the interpretation the longevity experiments, in which the elav -Gal4 drivers were used [ 39 41 ]. In addition, the CG16779 gene is predicted to encode a factor involved in regulation of Choline acetyltransferase (ChAT), which is responsible for the synthesis of the neurotransmitter acetylcholine [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…A number of genes within Q4 show expression variation between young and old animals in our study (Additional file 15 : Table S7). This set includes CG8032 , which is also the only member of a set of 39 lifespan-reducing loci identified in a gain-of-function screen that is implicated by QTL mapped in the present study [ 22 ], and Nmdmc , overexpression of which has been shown to extend lifespan in flies [ 81 ]. Given the number of genes within Q4, and the ample evidence of multiple candidates present in the region, it is not unlikely that more than one gene in the region is responsible for the QTL we map.…”
Section: Discussionmentioning
confidence: 99%
“…In model systems, two broad strategies can be implemented to identify genes and pathways impacting lifespan and age-related phenotypes: Mutational analyses, and mapping loci contributing to variation in lifespan in natural, or semi-natural laboratory populations. Given the relative ease with which large-effect mutations can be generated and interrogated in flies, multiple studies have screened large sets of induced mutations for their effects on lifespan (e.g., [ 21 , 22 ]), and detailed mechanistic studies targeting specific genes and pathways have added considerably to our understanding of the aging process. However, such loci may be distinct from those that harbor naturally-segregating sites underlying variation in lifespan (compare Tables one, two, and three in [ 23 ]).…”
Section: Introductionmentioning
confidence: 99%
“…To test this hypothesis, we checked the intestinal morphology of the larvae, revealing that LN diet causes shortening of the intestines in the control flies, which was prevented by AOX expression (Figure 3A). We next tested whether tissue-restricted expression of AOX could reproduce the pupal lethality observed with the ubiquitous expression system, by the use of a GAL4 driver supporting expression principally in cells of the gut, as well as some other epithelia (38)(39)(40). However, pupal viability remained as high as in the controls (Figure 3B), indicating that the lethal phenotype is a consequence of AOX expression in one or more other tissues, and could be a systemic effect in which the digestive tract is significantly affected, perhaps as part of a compensatory physiological response.…”
Section: Aox Expression Induces Functional and Morphological Changes In The Larval Digestive Systemmentioning
confidence: 99%